Hubungan Dukungan Suami dengan Angka Kejadian Post Partum Blues di Wilayah Kelurahan Bungursari Puskesmas Bungursari Kota Tasikmalaya - Iis Istianah; Riza Faulina (Universitas Malahayati Lampung, 2024)
ABSTRACT Postpartum blues or what is more commonly known by the public as baby blues is a psychological disorder experienced by mothers during the postpartum period. If not handled properly, this is prone to developing into postpartum depression or postpartum psychosis. The incidence of postpartum blues is between 50-70% of postpartum women, one in 10 women who have just given birth have a tendency to postpartum blues. The husband is the first and foremost support in providing social support to the wife before other parties provide it. To determine the relationship between husband's support and the incidence of post partum blues in mothers in the Bungursari Village, Bungursari Health Center, Tasikmalaya City. Researchers used quantitative methods with a correlational design with a cross-sectional approach. The time of this research was conducted from April to June 2023. The population in this study were all postpartum mothers in the Bungursari Village, Bungursari Health Center, Tasikmalaya City, totaling 35 people. Samples were taken using total sampling technique so that 35 people were taken. Data were analyzed using univariate analysis and chi square bivariate analysis. The results of the univariate study were obtained from 75 respondents, mostly 55 respondents (73.3%) had husband's support in the good category. The results of the chi-square test showed that p = 0.036 a= 0.05 with r = 0.25. There is a relationship between husband's support and the occurrence of postpartum blues in postpartum mothers in the Bungursari Village Area, Bungursari Health Center, Tasikmalaya City. Keywords: Husband Support, Postpartum Blues ABSTRAK Postpartum blues atau yang oleh masyarakat lebih sering dikenal dengan istilah baby blues merupakan suatu gangguan psikologis yang dialami ibu pada masa postpartum. Jika tidak tertangani dengan tepat hal ini rentan berkembang menjadi penyakit/gangguan mental postpartum depression atau postpartum psychosis. Angka kejadian postpartum blues antara 50-70% dari wanita pasca persalinan, satu dari 10 wanita yang baru saja melahirkan memiliki kecenderungan postpartum blues. Suami merupakan dukungan pertama dan utama dalam memberikan dukungan sosial kepada istri sebelum pihak lain yang memberikan. Untuk mengetahui hubungan dukungan suami dengan tingkat kejadian post partum blues pada ibu di Kelurahan Bungursari Puskesmas Bungursari Kota Tasikmalaya. Peneliti menggunakan metode kuantitatif dengan rancangan korelasional pendeketan cross sectional. Waktu penelitian ini dilakukan pada bulan April sampai dengan Juni 2023. Populasi pada penelitian ini adalah seluruh ibu postpartum di Kelurahan Bungursari Puskesmas Bungursari Kota Tasikmalaya sebanyak 35 orang. Sampel diambil menggunakan teknik total sampling sehingga diambil 35 orang. Data dianalisis menggunakan analisis univariat dan analisis bivariat chi square. Hasil penelitian univariat diperoleh dari 75 responden, sebagian besar sebanyak 55 responden (73.3%) memiliki dukungan suami pada kategori baik. Hasil uji chi-square menunjukkan hasil p = 0.036 a= 0.05 dengan r = 0.25. Terdapat hubungan antara dukungan suami dengan terjadinya postpartum blues pada ibu postpartum di Wilayah Kelurahan Bungursari Puskesmas Bungursari Kota Tasikmalaya. Kata Kunci: Dukungan Suami, Post Partum Blues